2011
DOI: 10.1007/s11075-010-9444-3
|View full text |Cite
|
Sign up to set email alerts
|

A unified kernel function approach to primal-dual interior-point algorithms for convex quadratic SDO

Abstract: Kernel functions play an important role in the design and analysis of primal-dual interior-point algorithms. They are not only used for determining the search directions but also for measuring the distance between the given iterate and the μ-center for the algorithms. In this paper we present a unified kernel function approach to primal-dual interior-point algorithms for convex quadratic semidefinite optimization based on the Nesterov and Todd symmetrization scheme. The iteration bounds for large-and small-upd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Among them, the interior-point methods (IPMs) gained much more attention than others [2,5]. Several, IPMs designed for linear 877 optimization (LO) have been successfully extended to CQSDO, (e.g., [4,14,17,19,22,23,24]), due to their polynomial complexity and practical efficiency.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among them, the interior-point methods (IPMs) gained much more attention than others [2,5]. Several, IPMs designed for linear 877 optimization (LO) have been successfully extended to CQSDO, (e.g., [4,14,17,19,22,23,24]), due to their polynomial complexity and practical efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…We note that similar algorithms are successfully prolonged to convex quadratic optimization over symmetric cone (CQSCO) (see [10,21]). For some other related interior-point algorithms based on the kernel functions we refer to [1,3,6,11,18,22,23,24,25]. A kernel function is a univariate strictly convex function which is defined for all positive real t and is minimal at t = 1 whereas the minimal value equals 0.…”
Section: Introductionmentioning
confidence: 99%
“…Many interior-point methods (IPMs) for linear optimization (LO) are successfully extended to (SDO) due to their polynomial complexity and practical efficiency. For an overview of these results, we refer to [1,2] and the references [3,4,5,6,7,8,9,10,11,12,13].…”
Section: Introductionmentioning
confidence: 99%
“…He showed that the primal-dual IPMs for solving SDO enjoys O(n Haseli [1] presented an interior-point algorithm for LO based on a new kernel function and obtained the best known iteration bound for large-update methods. Recently, Wang and Zhu [21] proposed a unified kernel function approach to primal-dual IPMs for CQSDO based on kernel functions which were previously introduced for LO in [2]. Later on, Zhang [23] presented a large-update interior-point algorithm for CQSDO based on a new kernel function and obtained its iteration complexity as O( √ n(log n) 2 log n ) for the CQSDO problems.…”
Section: Introductionmentioning
confidence: 99%